Human Capital and Education for Sustainable Development in a Global World - Catalin Chiriac (CES Working Papers, 2010)
The world continues to face various critical challenges such as: human-induced climate change, the rapid depletion of natural resources, the loss of biodiversity, increased poverty, the dependency of our economic systems on continuous growth in consumerism and so forth. Sustainable economic development focuses on the development of the economic infrastructure, in which the efficient management of our natural and human resources is crucially important. This paper presents on one hand the main steps made for creating, defining and applying the principles of sustainable development and on the other hand, it tries to highlight the role of education seen here as a powerful factor in modeling our most important resource: human capital.
Keywords: 330; sustainable development; human capital; education; European Union